PERAN KELEMBAGAAN MANCUANA POPA’ANO DALAM MENJAGA KELESTARIAN HUTAN KAOMBO DI KELURAHAN GONDA BARU KECAMATAN SORAWOLIO KOTA BAU-BAU - Sahril Sahril; La Nalefo; Nur Isiyana Wianti (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This study aims to determine the social system in society in Gonda Baru Village. To find out the institutional role of "Mancuana Popa`Ano" in the management of the kaombo forest in Gonda Baru Village. The data analysis used is descriptive qualitative. The research method used is a qualitative analysis method. The data collection process is carried out by means of surveys, interviews, literature studies, and documentation. The beginning of the formation of Mancuana Popa`Ano in the Cia-Cia tribe began in the Age of the Sultanate of Buton. Based on the narrative of Mr. Samsudin at the time of the Sultanate of Buton. In carrying out his duties and functions, the role of Mancuna Popa`Ano does not change along with the change in leadership. The role of Mancuana Popa`Ano is to give peace to the indigenous people of Gonda Baru Village, to provide comfort, to help indigenous peoples in solving problems, to protect the Kaombo forest, to maintain the prevailing customs by teaching youth and women to love custom. Kaombo forest is a protected forest to preserve the forest and protect the springs. The role of Mancuana Popa`Ano in preserving the Kaombo forest is to direct the Gonda Baru indigenous people to protect the forest and the community to be given an understanding of the importance of forest preservation, especially the Kaombo forest. The name of the rule in protecting the forest from Mancuana Popa`Ano is Kabori. An illustration of the success of protecting the Kaombo forest by Mancuana Popa`Ano is that until now the Kaombo forest is still preserved and at this time Gonda Baru Village has been named a climate village.